Borrowing High versus Borrowing Higher: Price Dispersion and Shopping Behavior in the U.S. Credit Card Market - Stango, Victor; Zinman, Jonathan (Review of Financial Studies, 2016)
We document substantial cross-individual dispersion in U.S. credit card borrowing costs, even after controlling for borrower risk and card characteristics. That remaining dispersion arises because cross-lender pricing heterogeneity generates dispersion in annual percentage rate (APR) offers to borrowers, and borrowers vary in shopping intensity. Our empirics match administrative data to self-reported card shopping intensity and use instruments suggested by fair lending law to account for the endogeneity between APRs and search. The results show that shoppers versus nonshoppers pay APRs as different as those paid by borrowers in the best versus worst credit score deciles. We discuss implications for policy and practice. Received August 2, 2014; accepted July 7, 2015 by Editor Philip Strahan.